Muckenhoupt–Wheeden theorem for generalized f-Riesz-type potentials - Knopova, V. (Український математичний журнал, 2008)
We obtain the Muckenhoupt-Wheeden theorem for some class of potentials. As a consequence, we describe the equivalent norm in the generalized Bessel potential space of negative order.